Analisis Pengaruh Korupsi Terhadap Kemiskinan Di Indonesia Selama Periode 2001-2021 - Hamida, Safira; Ahmad, Abdul Aziz (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
This study examines the impact of corruption on poverty in Indonesia during the period 2001–2021, while considering other macroeconomic variables such as the Human Development Index (HDI), unemployment, and inflation. Using secondary data, the research applies multiple linear regression. The results reveal that corruption has a positive and significant effect on poverty. Conversely, HDI has a negative and significant effect, showing that improved human development reduces poverty. Unemployment also shows a positive relationship with poverty, while inflation has a weaker but still positive impact. These findings underscore the importance of anti-corruption measures, investments in human capital, job creation policies, and inflation control to effectively reduce poverty in Indonesia.